1996
DOI: 10.1097/00000542-199611000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Immunoisolated Xenogeneic Chromaffin Cell Therapy for Chronic Pain

Abstract: This study represents the first successful trial of encapsulated xenogeneic cells in humans. The preliminary findings of pain reduction warrant the initiation of a randomized, double-blind phase II study to evaluate the potential efficacy of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(54 citation statements)
references
References 27 publications
1
52
0
1
Order By: Relevance
“…Previous studies in our and other laboratories have demonstrated that transplants of adrenal medullary chromaffin cells into the subarachnoid space of the spinal cord can attenuate pain responses in a variety of animal models and offers a promising avenue for clinical pain management (Brewer and Yezierski 1998;Buchser et al 1996;Burgess et al 1996;Décosterd et al 1998;Hains et al 1998;Hama and Sagen 1993;Lazorthes et al 1995;Ortega-Alvaro et al 1997;Sagen et al 1990;Siegan and Sagen 1997;Vaquero et al 1991;Winnie et al 1993;Yu et al 1998). Although the transplanted cells appear to produce some of their antinociceptive effects via local release of pain-reducing analgesic agents, including catecholamines and opioid peptides, into the host spinal CSF (Sagen and Kemmler 1989;Sagen et al 1991), recent studies have indicated that these transplants can also produce neuroplastic changes in the pain processing circuitry of the spinal cord, including restoration of spinal inhibitory neurons and decreased c-fos activation in response to persistent pain (Ibuki et al 1997;Sagen and Wang 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in our and other laboratories have demonstrated that transplants of adrenal medullary chromaffin cells into the subarachnoid space of the spinal cord can attenuate pain responses in a variety of animal models and offers a promising avenue for clinical pain management (Brewer and Yezierski 1998;Buchser et al 1996;Burgess et al 1996;Décosterd et al 1998;Hains et al 1998;Hama and Sagen 1993;Lazorthes et al 1995;Ortega-Alvaro et al 1997;Sagen et al 1990;Siegan and Sagen 1997;Vaquero et al 1991;Winnie et al 1993;Yu et al 1998). Although the transplanted cells appear to produce some of their antinociceptive effects via local release of pain-reducing analgesic agents, including catecholamines and opioid peptides, into the host spinal CSF (Sagen and Kemmler 1989;Sagen et al 1991), recent studies have indicated that these transplants can also produce neuroplastic changes in the pain processing circuitry of the spinal cord, including restoration of spinal inhibitory neurons and decreased c-fos activation in response to persistent pain (Ibuki et al 1997;Sagen and Wang 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the initiation of clinical trials at several centers, with promising outcomes (Buchser et al 1996;Burgess et al, 1996;Lazorthes et al 1995;Winnie et al 1993). Since chromaffin cells produce and secrete several potential pain-reducing neuroactive substances, including opioid peptides and catecholamines, a possible mechanism for this pain reduction is via inhibition of spinal pain transmission pathways.…”
Section: While Transplants Of Adrenal Medullary Cells Into the Spinalmentioning
confidence: 99%
“…All of these avoid vascular anastomoses, thus diminishing the stimulus for immunologic rejection, and several use various modes of immunoprotection that may preclude the need for exogenous immunosuppression. Past and current clinical trials have attempted to ameliorate refractory pain in terminal cancer patients by using bovine adrenal preparations (16) (60), or to treat sepsis by hemoperfusion through pig spleen (88). Clinical trials attempting to functionally "cure" diabetes by implanting porcine pancreatic islet cells have also been conducted (41,46,101).…”
Section: Modern History Of Xenotransplantationmentioning
confidence: 99%
“…Lumbar puncture can be easily performed in most instances, but is contraindicated in patients with increased intracranial pressure from an intracranial expansion. This method has been applied by Aebischer and colleagues to treat patients with chronic pain or amyotrophic lateral sclerosis, using encapsulated cells releasing catecholamines and CNTF, respectively Buchser et al, 1996). In both trials, they used a device comprising a 5-cm-long hollow ber membrane containing cells in a matrix and a silicon tether.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Nanogram levels of CNTF were measured in patients' CSF for at least 17 weeks posttransplantation, whereas it was undetectable before implantation. In another study performed by Buchser et al (1996), patients with chronic pain were implanted with similar polymers with chromaf n cells releasing catecholamines with a strong analgesic effect. Even though the increase in CSF concentrations of the substance was not signi cant in the lumbar puncture aspirates, all patients using epidural morphine decreased the intake after implantation.…”
Section: Biodistributionmentioning
confidence: 99%